LINGUISTIC FEATURES OF EVALUATIVE STANCE: FINDINGS FROM RESEARCH ARTICLE DISCUSSIONS - Khamkhien, Attapol (Indonesian Journal of Applied Linguistics, 2014)
Abstract: Recent research (e.g., Hunston 2007; Hyland 1999; 2008; 2009) has marked and evidenced the importance of effectively using linguistic features as a major component in expressing stances and as an essential part of the shared knowledge of a professional discourse community by giving space for negotiation and evaluation of viewpoints.  The present study is concerned with the use of the expression of evaluation in academic discourse, focusing on some communicative strategies for indicating stance.  With the corpus-based approach, research articles on applied linguistics and language teaching selected from top-ten journals were systematically complied and analyzed.  The results revealed that professional and experienced writers variably exploit stance markers including epistemic modality, extraposed ‘it’, communication verbs, and personal pronouns in terms of different functional types of evaluative stance.  The findings highlight the importance of understanding the use of stance devices in academics, facilitating a better understanding of novice readers and writers when writing academic productions.  Pedagogically, the description of this study contributes to ways to improvement of practical language and academic writing courses to suit the discourse community. Keywords: Corpus, evaluative stance, discourse, academic research